2013
DOI: 10.4028/www.scientific.net/msf.773-774.448
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Highly Filled Iron-ABS Composites in Injection Molding for FDM Wire Filament

Abstract: Abstract. This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…Other researchers have observed mixed hardness results for their composite specimens. There was no significant change but only slight increment in hardness between pure ABS (100% ABS) and ABS–iron material with (ABS 50%, Iron 24%, 26% surfactant), (ABS 48%, Iron 26%, 26% surfactant) and (ABS 46%, Iron 29%, 25% surfactant) which was recorded to have hardness value at 62.68%, 63.53% and 69.47% respectively reported by Sa'ude et al . Jan et al also reported the hardness test by Shore‐D showed an increase from 71.84 for pure material up to 74.28 for ABS with 5% MWCNT .…”
Section: Resultsmentioning
confidence: 78%
“…Other researchers have observed mixed hardness results for their composite specimens. There was no significant change but only slight increment in hardness between pure ABS (100% ABS) and ABS–iron material with (ABS 50%, Iron 24%, 26% surfactant), (ABS 48%, Iron 26%, 26% surfactant) and (ABS 46%, Iron 29%, 25% surfactant) which was recorded to have hardness value at 62.68%, 63.53% and 69.47% respectively reported by Sa'ude et al . Jan et al also reported the hardness test by Shore‐D showed an increase from 71.84 for pure material up to 74.28 for ABS with 5% MWCNT .…”
Section: Resultsmentioning
confidence: 78%
“…Currently, metal filled in the polymer matrix has become an alternative material used in FDM machine. Some researcher used a mix material of ABS-Iron [2,3,9,10,11] and ABS-copper [12,13]. Masood et al and Nikzad et al mentioned that the critical properties' requirements for high-quality composite are depending on the desired viscosity, strength and modulus.…”
Section: Introductionmentioning
confidence: 99%
“…The metal powders also affected the glass transition of the SAN phase of ABS, as shown in Table 5 and Figure 9. It is known that the T g of ABS is at approximately 100 • C and relates to the glassy-rubbery transition of the SAN grafting block [25,33,39,57]. The maxima of the tan(δ) DMA curves obtained with DMA displayed the same trend of change in ascending order as exhibited by G and η*.…”
Section: Viscoelastic Propertiesmentioning
confidence: 69%
“…Compared to neat ABS, the composites showed a higher hardness and elastic modulus. Significant improvements in ABS's mechanical and thermal properties suggest that a suitable selection of material composition and other parameters may lead to a FDM filament of great potential, yielding high-performance, functional prototypes for a wide range of applications manufactured with the FDM process [7,25].…”
Section: Introductionmentioning
confidence: 99%